Impact of tribo-morphological transformation of graphene on the viscosity of engine oils - Rasheed, A. K. *; Khalid, Mohammad *; Gupta, T.C.S.M; Hikmat, S. (2018)
One of the major factors that determines the choice of engine oil is its viscosity. This research investigates the impact of graphene on the viscosity of engine oil before and after IC engine operation. Morphological changes of the graphene flakes have been studied to understand its dependency on the rheological performance of engine oil. Graphene based nanolubricants were synthesized to meet API SN/CF 20W50 grade. Scanning electron microscopy graphs show that the graphene flakes undergo tribomorphological transformations to become tubes, helical coils and percolated structures. However, such changes do not significantly impact the viscosity of engine oil throughout its life-cycle.